Challenges and developments of bioretention facilities in treating urban stormwater runoff; A review - Zakaria, Nor Azazi; Ghani, Aminuddin Ab; Takaijudin, Husna (Iran Solid Waste Association (ISWA), 2016)
Bioretention or rain garden is a preferable low impact development (LID) approach due to its characteristics which reflect natural water cycle processes. However, this system is still little understood and quite complicated in terms of design and implementation due to many technical considerations. Hence, this paper gives a review of the challenges and developments for the use of bioretention facilities to enhance its capabilities in attenuating peak flow and treating stormwater runoff particularly in urban areas. This paper reviews the main aspects of bioretention which are stormwater hydrologic, hydraulic and treatment performance. Some of the limitations during the implementation of this natural approach are highlighted in design configuration and the public perception towards this new approach. It is concluded that the bioretention approach is one of the sustainable solutions for stormwater management that can be applied either for individual systems or regional systems.